Novel methods for quantifying individual host response to infectious pathogens for genetic analyses - Doeschl-Wilson, Andrea B.; Bishop, Steve; Kyriazakis, Ilias; Villanueva, Beatriz (Frontiers in Genetics, 2012)
Here we propose two novel approaches for describing and quantifying the response of individual hosts to pathogen challenge in terms of infection severity and impact on host performance. The first approach is a direct extension of the methodology for estimating group tolerance – the change in performance with respect to changes in pathogen burden in a host population – to the level of individuals. The second approach aims to capturethe dynamic aspects of individual resistance and tolerance over the entire time course of infections. In contrast to the first approach, which provides a means to disentangle host resistance from tolerance, the second approach considers the combined effects of host resistance and tolerance. Both approaches provide new individual phenotypes for subsequent genetic analyses and come with specific data requirements. Consideration of individual tolerance also highlights some of the assumptions hidden within the concept of group tolerance, indicating where care needs to be taken in trait definition and measurement.